A Critical Analysis of the Rights of an Accused Person During Trial in Somalia - Jansky, Okiya Jimmy (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
This study focuses on critical analysis of the rights of an accused person during trial in Somalia. The rights of accused person in Somalia have become a contentious and serious issue owing to the on-going civil war in Somalia which has now lasted for two decades. The doctrinal research methodoly was used to collect and analyse the data used in the study. The relevant secondary data were collected through documetary review where relevant data was collected from different books, national and international legal statutues and scholarly publications of scholars in relation to the rights of an accused person during trial in Somalia. The study employed a systematic procedure to analyse documentary evidence and answer specific research questions in the study through repeated review, examination and interpretation of the data in order to gain meaning and empirical knowledge of the construct being studied. The study analysed the rights of an accused person under the various national laws of Somalia, the various forms of violation of the rights of an accused person in Somalia and the causes of the violation of the rights of an accused person in Somalia. The main findings of the study revealed that the various and sufficient rights of an accused person during train in Somalia, as provided by the Provisional Constitution of Somalia, 2012, and the Criminal Code Act of Somalia, 1963, include: right to liberty and security, right to be informed promptly of the offence charged, right to fair and speedy trial, right to humane treatment, the right to be presumed innocent until proven guilty, right to a fair hearing, right to defend himself or herself, right to counsel, right to be informed of the nature offense an accused person has committed, the right to an interpreter, the right to be present at the trial, right to be brought promptly before a capable court, the right to habeas corpus, the right to apply for bail, the right not to be compelled to testify against himself or herself, right to examine evidence or witnesses and the right to appeal. However, these rights are neither being promoted nor protected in Somalia; instead they are being violated in various ways which they encompass: violation of arrest procedures and unfair and cruel treatment of accused person, arbitrary arrest, denial of fair public trial, violation of trial procedures, unlawful treatment and detention of political prisoners and accused persons being caused by structural and legal ambiguity, the continuous practise of legal pluralism, the existence of broken chain in the justice system, high level of corruption and mismanagement, military interference. The study recommended that the Federal Government of Somalia through its three organs should enact new law, promote fair and procedural arrest of accused train and sensitise the people about their rights as an accused and should initiate good policies and project that can foster the promotion and protection of human rights in the sphere of accused person’s protection during and after trial in Somalia.